Zombies on the Brink : Evidence from Japan on the Reversal of Monetary Policy Effectiveness - Hong, Gee Hee (IMF Working Papers; Working Paper ;, 2021)
How does unconventional monetary policy affect corporate capital structure and investment decisions? We study the transmission channel of quantitative easing and its potential diminishing returns on investment from a corporate finance perspective. Using a rich bank-firm matched data of Japanese firms with information on corporate debt and investment, we study how firms adjust their capital structure in response to the changes in term premia. Investment responds positively to a reduction in the term premium on average. However, there is a significant degree of cross-sectional variation in firm response: healthier firms increase capital spending and cash holdings, while financially vulnerable firms take advantage of lower long-term yields to refinance without increasing investment.